Adsorption Hysteresis of Nitrogen and Argon in Pore Networks and Characterization of Novel Micro- and Mesoporous Silicas. - Thommes, Matthias; et al. (Langmuir, 2006)
The authors report results of nitrogen and argon adsorption expts. performed at 77.4 and 87.3 K on novel micro/mesoporous silica materials with morphol. different networks of mesopores embedded into microporous matrixes: SE3030 silica with wormlike cylindrical channels of mode diam. of ∼95 Å, KLE silica with cagelike spheroidal pores of ca. 140 Å, KLE/IL silica with spheroidal pores of ∼140 Å connected by cylindrical channels of ∼26 Å, and, also for a comparison, on Vycor glass with a disordered network of pores of mode diam. of ∼70 Å. The type of hysteresis loop formed by adsorption/desorption isotherms is detd. by different mechanisms of condensation and evapn. and depends upon the shape and size of pores. Adsorption expts. performed with different adsorptives allow for detecting and sepg. the effects of pore blocking/percolation and cavitation in evapn. Cavitation-controlled evapn. occurs in ink-bottle pores with the neck size smaller than a certain crit. value. In this case, the pressure of evapn. does not depend upon the neck size. In pores with larger necks, percolation-controlled evapn. occurs, as obsd. for nitrogen (at 77.4 K) and argon (at 87.3 K) on porous Vycor glass. The authors elaborate a novel hybrid nonlocal d. functional theory (NLDFT) method for calcns. of pore size distributions from adsorption isotherms in the entire range of micro- and mesopores. The NLDFT method, applied to the adsorption branch of the isotherm, takes into account the effect of delayed capillary condensation in pores of different geometries. The pore size data obtained by the NLDFT method for SE3030, KLE, and KLE/IL silicas agree with the data of SANS/SAXS techniques. [on SciFinder(R)]
Keywords: adsorption desorption hysteresis nitrogen argon pore network